PEKERJA MIGRAN SIRKULER DALAM PENINGKATAN KESEJAHTERAAN SOSIAL KELUARGA DI DESA NGEMBOH KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - Yulianto, Fadly; Furqan, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Research on circular migrants and improving their family's social welfare has been carried out in Ngemboh Village, Ujungpangkah District, Gresik Regency. This study involved 30 respondents who came from 30 families whose members were circular migrant workers. Data were collected through interviews, observation, and document review, then analyzed descriptively and qualitatively. The results show that every family supports its members to become circular migrant workers. In addition to the limited employment opportunities in the area of origin, the main reason for becoming a circular migrant worker is to meet economic needs and improve family welfare. The money earned at this time was bought in the form of milling machines and chainsaws, as well as pets to raise. Actually, this method has good potential to advance the business sector in the area of origin. Therefore, local governments in villages or sub-districts are advised to form microfinance institutions to manage some of their funds and as savings or investments for business financing. Business actors can be encouraged through the formation of an economic community initiated by the Ministry of Social Affairs through the local Social Service. The contribution of this research to the wider community is to provide an overview of circular migrant workers in the organization and form of their work. Financial management and any impacts that occur both personally and as a community in society.Keywords: Circular Migrant Workers; Family Social Welfare.Abstrak: Penelitian tentang migran sirkuler dan peningkatan kesejahteraan sosial keluarganya telah dilakukan di Desa Ngemboh Kecamatan Ujungpangkah Kabupaten Gresik. Penelitian ini melibatkan 30 responden yang berasal dari 30 keluarga yang anggotanya merupakan pekerja migran sirkuler. Data dikumpulkan melalui wawancara, observasi, dan telaah dokumen, kemudian dianalisis secara deskriptif dan kualitatif. Hasilnya menunjukkan bahwa setiap keluarga mendukung anggotanya menjadi pekerja migran sirkuler. Selain terbatasnya kesempatan kerja di daerah asal, alasan utama menjadi pekerja migran sirkuler adalah untuk memenuhi kebutuhan ekonomi dan meningkatkan kesejahteraan keluarga. Uang yang diperoleh saat ini dibelikan dalam bentuk mesin giling dan gergaji mesin, serta hewan peliharaan untuk diternak. Sebenarnya cara ini memiliki potensi yang baik untuk memajukan sektor bisnis di daerah asal. Oleh karena itu, pemerintah daerah di desa atau kecamatan disarankan untuk membentuk lembaga keuangan mikro untuk mengelola sebagian dana mereka dan sebagai tabungan atau investasi untuk pembiayaan usaha. Pelaku usaha dapat digalakkan melalui pembentukan masyarakat ekonomi yang diinisiasi oleh Kementerian Sosial melalui Dinas Sosial setempat. Kontribusi penelitian ini bagi masyarakat luas adalah untuk memberikan gambaran terkait pekerja migran sirkular dalam mengatur dan bentuk dari pekerjaan mereka. Pengelolaan keuangan serta dampak apa saja yang terjadi baik secara pribadi maupun secara komunitas dalam masyarakat.Kata Kunci: Pekerja Migran Sirkuler; Kesejahteraan Sosial Keluarga.